The molecular motion of bovine serum albumin under physiological conditions is ion specific. Issue 30 (18th March 2015) - Medda, Luca; Monduzzi, Maura; Salis, Andrea
Abstract : Specific ion effects on the Brownian motion of BSA protein under physiological conditions give new useful insights into the electrolyte–protein interactions and the molecular mechanisms involved in the Hofmeister effect. Abstract : Specific ion effects on the Brownian molecular motion of BSA protein under physiological conditions are investigated. New useful insights into Hofmeister phenomena related to electrolyte–protein interactions are presented.